TaleSpin. Volume 1 [videorecording (DVD)] (Disney DVD., 2013)
The Higher for hire crew--including Baloo the bear, navigator Kit Cloudkicker, and boss Rebecca Cunningham--experience adventures piloting cargo and battling foes, including Don Karnage and his evil Air Pirates.